Antara Regulasi dan Realitas Sosial: Hambatan Penegakan Hukum terhadap Perusakan Hutan Konservasi di Pohuwato: Between Regulation and Social Reality: Barriers to Law Enforcement Against Conservation Forest Destruction in Pohuwato - Mohammad Ainal Ahyat; Fenty U Puluhulawa; Nurvazri Achir (Jurnal Hukum Bisnis, 2026)
The Panua Nature Reserve in Pohuwato Regency is a legally protected conservation area. However, in practice, it still faces various forms of destruction, including illegal gold mining, encroachment, and the illegal exploitation of forest products, raising questions about the effectiveness of law enforcement. This study aims to analyze the implementation of law enforcement against forest destruction in the area and identify factors that hinder its effectiveness from the perspective of legal certainty, ecological justice, and legal benefits. The study uses a normative legal approach supported by an empirical dimension through the study of legislation, analysis of court decisions, review of reputable scientific literature, and interviews with law enforcement officials and the Natural Resources Conservation Agency. Data were analyzed qualitatively using deductive and inductive reasoning, along with source triangulation, to ensure the consistency and validity of the findings. The results show that normatively, the legal instruments are adequate. However, their effectiveness is hampered by limited oversight, imbalances between the threat of sanctions and criminal practices, suboptimal tracing of intellectual actors, and the lack of integration of ecological restoration in court decisions. Law enforcement tends to be repressive and procedural, thus failing to deter and sustain environmental protection fully. Therefore, strengthening institutional coordination, integrating restorative sanctions, and a preventative approach based on the welfare of surrounding communities are prerequisites for achieving substantive environmental law effectiveness.